FROM PRODUCTION TO SECURITIZATION: the scalar articulation between the housing market and financial income - Abreu, Marlon Altavini de [UNESP]; Shimbo, Lucia Zanin (Univ Estado Rio Janeiro, 2024)
The paper examines the interactions between the private housing market and the leverage dynamics and indebtedness of large publicly traded developers between the years 2011 and 2023 in Brazil, in which real estate incomes are articulated with the capitalization of financial incomes. The importance of this articulation is highlighted to understand the relationships between local and national scales in the real estate sector, as well as the impacts of financial investment flows in different locations of the urban network. The focus is on the spatial strategies of MRV&Co, the largest Brazilian company in the residential segment, in adopting real estate securitization to finance its developments. The work is structured around the securitization issuances originated by the company between the years analyzed. Each of these securities was meticulously evaluated with the intention of measuring information related to the negotiable amounts and the types of developments that originated the operations. It is concluded by emphasizing the relevance of analyzing the company's securitization issuances to understand the interactions between local and national scales in the real estate sector.
Keywords: financialization; securitization; real estate receivables certificates; housing production; MRV&Co